Faktor-Faktor Penentu Adopsi E-Wallet Ovo Di Provinsi Jawa Timur - Chowal Jundy Kumoro; Basuki Rachmat (Jurnal Manajerial, 2022)
Background – For several years the existence of the internet and smartphones has changed the lives of the wider community by making an important role in the development of digital technology. One of them is the development of innovation in the field of financial services. Electronic wallet (E-wallet) or digital wallet is part of financial technology that provides services or features in financial payment methods that utilize internet services. People can transact faster by utilizing digital payment methods. Purpose – Determine and analyze the effect of perceived usefulness variable, relative advantage variable, social influence variable, risk perception variable, cost variable on behavioural intention. Test and analyze the effect of behavioural intention on consumer adoption of OVO in East Java Province. Design/ Methodology/ Approach – This study used a sample of 130 respondents using questionnaires distributed to respondents online using Google forms. The data processing method used in this research is Partial Least Square (PLS) with WarpPLS 6.0 software. The sample in this study is OVO users who live in East Java Province. The type of sampling in this research is purposive sampling. Results and Discussion– Perceived usefulness and relative advantages have a significant and positive effect on behavioural intention. Social influence, perceived risk and cost have no impact on behavioural intention. behavioural intention has a significant positive effect on OVO adoption. Conclusion – OVO users are presented with the many features and conveniences offered. In research, users use this service because these users feel benefits such as being able to make transactions faster and feel more comfortable than cash payments. In addition, the decision to use OVO services is not influenced by social influences, perceived risk and cost. Research implications – Expanding collaboration with new merchants and adding new features to make it easier to use and improve the performance of service users. Enriching features that users can take advantage of in managing and controlling their finances. The need for a reward program for service users who recommend OVO. OVO needs to provide certainty to users that OVO services are safe from possible risks such as malfunctions and privacy security. Research limitations – This study involving 130 respondents was undertaken with the sample of user of OVO in east java province and sample may not be a representation of the population. In this study only limited to the variables of Perceived usefulness, Relative Advantage, Social Influence, Perceived Risk, Cost, Behavioural Intention and OVO Adoption.